(untitled) (Research, Society and Development, 2023)
Introduction: Migraine, also known as migraines, is a chronic neurological condition that affects millions of people worldwide, characterized by pulsating headaches and symptoms such as emesis, photophobia and phonophobia. The causes are complex, including genetic factors, disturbances in cerebral blood flow and dysfunctions in the autonomic nervous system. In this review, we will explore the role of some transcutaneous electrical stimulation treatments, as well as analyzing their clinical evidence, mechanisms of action and efficacy, providing valuable information for the management of this complex condition. Methodology: In 2023, we conducted an integrative review in six stages: (1) we formulated the research question, (2) we searched for articles, (3) we applied inclusion/exclusion criteria, (4) we selected 8 studies, (5) we analyzed the abstracts and (6) we read the full texts for detailed analysis. Results: There are several treatments available to treat migraine using authorized neuromodulator devices. The studies analyzed show significant efficacy in the treatment of chronic and episodic migraine, although more studies are needed to elucidate their functionality. Conclusion: Electrical stimulation is emerging as a promising and welcome alternative for the treatment of migraine. As research advances and new technologies are developed, hope and relief are brought to patients facing the symptoms of migraine. However, it is important to recognize that electrical stimulation may not be equally effective for all individuals, necessitating discussions with the healthcare professional responsible.